DINAMIKA CITY BRANDING KOTA SURAKARTA DALAM MENARIK MINAT BERKUNJUNG WISATAWAN - Dyah Ayu Pandansari; Eko Priyo Purnomo; Aulia Nur Kasiwi (Jurnal Ilmu Pemerintahan Widya Praja, 2020)
This study aims to identify the role of city branding in increasing the number of tourist visits in the city of Surakarta. The research method used is library research method. Data collection method used is the documentation method. The data analysis technique used is content analysis. The results of this study are city branding is an effort of a city to maintain the existence of the excellence of its region in global competition through logos, taglines, symbols, and slogans. This is an important element in the development of aspects of life in the City, as well as Surakarta, which feels that in an effort to improve the quality of the city, it is necessary to carry out branding to the international world. Thus, city branding in the city of Surakarta uses the tagline "Solo The Spirit Of Java" to describe the identity of the city of Surakarta to the world that the city of Surakarta is the center of Javanese cultural civilization so that it declares itself that Solo is the soul of Java. The strategy of the Surakarta city government in order to attract tourists to visit is through cultural attractions, arts and cultural festivals, and the provision of facilities and infrastructure that are able to accommodate the needs of tourists. In addition, the government also cooperates with the community, and the private sector or external bureaucrats in conducting branding communication. However, communication and consistency in promoting branding must be accompanied by synergy between the actors involved so as to achieve the main objectives of city branding. The recommendation for the government in branding is the consistency of branding that is used as a form of identity of the city of Surakarta because in the tagline "Solo The Spirit Of Java" there are several sub-branding that are also marketed to the public.